Spatial distribution of the burrows of Porcellio albinus in the coastal area of Zarat (Gabès, Tunisia). Issue 3 (4th May 2017) - Medini-Bouaziz, Lamia; El-Gtari, Mohamed; Hamaied, Sonia; Charfi-Cheikhrouha, Faouzia
Abstract : Among the desert-dwelling Porcellio species, widespread in southern Tunisia, only Porcellio albinus exhibits a burrowing behaviour. In this study we investigated how P. albinus "choose" to dig their burrows, especially through the study of their burrow densities both in the nebkas and in flat, sandy-surface habitats; the direction of the openings of the burrows; and the influence of wind and vegetation type on the spatial distribution of P. albinus burrows in the nebkas. Several field samplings were carried out in the sandy coastal area of Zarat (Gabès, in the south-eastern part of Tunisia) between January and December 2013. The mean densities of burrows in the two habitats – nebkas and flat, sandy surfaces – were not significantly different. A low positive correlation was observed between burrow density and nebka area. In each nebka, the burrows of P. albinus were localised within a circular belt in a sector facing towards the south, thus avoiding the main wind direction (E–NE). P. albinus prefers to dig their burrows on nebkas covered with Astragalus armatus and Stipagrostis pungens, and avoids those covered with Calicotome villosa . The absence of burrows at the top of the nebkas might be caused by their exposure to sunlight and drying. The lack of burrows at the base of the nebkas is assumed to be the consequence of the presence of non-porous and non-permeable substratum in direct contact with this base. This substratum creates a barrier, which prevents P. albinus from digging sufficiently deep burrows.